Survey of Infection Control Knowledge, Attitudes and Practices among Senior Dental Students at the University of Georgia - Chitaladze, Tamta; Kazakhashvili, Nata (Caucasus Journal of Health Sciences and Public Health, 2019)
Aim: The aim of this study was to evaluate knowledge, attitudes, and practices of infection control among senior dental students. Methods: A questionnaire study was conducted among 102 voluntarily participated third, fourth and fifth year dental students of the University of Georgia. It included 20 close-ended questions related to vaccination status, barrier techniques, Universal Precautions, students' selfassessment of knowledge about infection control issues, transmission of infection at a dental clinic, etc. Results: Only 31% of students believe that all patients are potentially infected; Only 40% agree to treat patients with infectious diseases; 34,3% do not consider the used personal protective equipment as hazardous waste; Only 44,4% think that used dental hand pieces must be autoclaved; Compliance with the use of protective barriers was high with the exception of protective eyewear and head cap. Only 48% remove gloves and musk while walking around in clinic; 75,3% believe that infection control should be studied as an independent subject in dentistry. Conclusion: A better knowledge of infection control is essential for safe practice of dentistry. Efforts are needed to motivate students in the correct and routine use of infection control measures. This will ensure provision of better and safer dental healthcare services for the population.